Nonlinear Analysis of Seismic Vulnerability in Mass Irregular Reinforced Concrete Buildings - Chawe, AeintMyet; Nang Su Le'. Mya Thwin (The Indonesian Journal of Computer Science, 2025)
With Myanmar's growing population, buildings adapt through architectural and functional irregularities. However, such irregular structures are more susceptible to earthquake damage than regular ones. This study develops a vulnerability index for a 143-ft, 12-story reinforced concrete condominium building with mass irregularities in Mandalay, designed per ASCE/MNBC seismic codes. Mass irregularity is considered at three locations in the same condominium reinforced concrete building: the lower, middle, and upper thirds. By evaluating these three locations, the study investigates how the position of mass irregularity influences a building's seismic vulnerability in pushover (nonlinear) analysis. Guidelines provided by the HAZUS-MH MR4 technical manual have been used to develop fragility curves. Based on the study analyzing the structural vulnerability of irregular frame buildings by plotting fragility curves and determining a vulnerability index based on plastic hinge formation, the VI values of bottom mass, middle mass, and top mass building were 0.71, 0.00, and 0.94 respectively. It appears that the maximum vulnerability index value is observed in the top mass irregular building. Among all irregular buildings, the top mass irregular building was found to be more vulnerable, and the middle mass irregular building was found to perform better than others.